Memory T cells: promising biomarkers for evaluating protection and vaccine efficacy against leishmaniasis - Nateghi-Rostami, Mahmoud; Sohrabi, Yahya (Frontiers in Immunology, 2024)
Understanding the immune response to Leishmania infection and identifying biomarkers that correlate with protection are crucial for developing effective vaccines. One intriguing aspect of Leishmania infection is the persistence of parasites, even after apparent lesion healing. Various host cells, including dendritic cells, fibroblasts, and Langerhans cells may serve as safe sites for latent infection. Memory T cells, especially tissue-resident memory T cells (TRM), play a crucial role in concomitant immunity against cutaneous Leishmania infections. These TRM cells are longlasting and can protect against reinfection in the absence of persistent parasites. CD4+ TRM cells, in particular, have been implicated in protection against Leishmania infections. These cells are characterized by their ability to reside in the skin and rapidly respond to secondary infections by producing cytokines such as IFN-γ, which activates macrophages to kill parasites. The induction of CD4+ TRM cells has shown promise in experimental immunization, leading to protection against Leishmania challenge infections. Identifying biomarkers of protection is a critical step in vaccine development and CD4+ TRM cells hold potential as biomarkers, as their presence and functions may correlate with protection. While, recent studies have shown that Leishmania-specific memory CD4+ T cells subsets are present in individuals with a history of cutaneous leishmaniasis, further researches are needed to characterize CD4+ TRM cell populations. Overall, this review highlights the importance of memory T cells, particularly skin-resident CD4+ TRM cells as promising targets for developing effective vaccines against leishmaniasis and as biomarkers of immune protection to assess the efficacy of candidate vaccines against human leishmaniasis.